2023
DOI: 10.18805/lr-5127
|View full text |Cite
|
Sign up to set email alerts
|

Potential Foliar Chemicals for Enhancing Yield and Drought Tolerance in Leguminous Crops: A Review

A. Mohammed Ashraf,
H.A. Archana,
M.R. Naveen Kumar
et al.

Abstract: In pulse crops, synchronized flowering altered the source-sink relationship due to the rapid translocation of nutrients from leaves to the developing pods. Additional nutrition through foliar feeding plays a vital role in pulse production by stimulating root development, nodulation, energy transformation, various metabolic processes and increasing pod setting, thereby increasing the yield. Many researchers are trying to reduce transpiration losses, flower shedding and maximizing productivity, foliar applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Kavitha et al [ 24 ] reported that the foliar application of TNAU pulse wonder at a 2% concentration during the flowering and pod formation stages improved the number of flowers, given in plant −1 , and green pod yield, given in ha −1 . Similarly, Ashraf et al [ 25 ] reported that the foliar application of TNAU pulse wonder improved the seed yield in pulses. El-Fouly et al [ 26 ] reported that the foliar application of nutrients to maize resulted in increased grain yield.…”
Section: Introductionmentioning
confidence: 98%
“…Kavitha et al [ 24 ] reported that the foliar application of TNAU pulse wonder at a 2% concentration during the flowering and pod formation stages improved the number of flowers, given in plant −1 , and green pod yield, given in ha −1 . Similarly, Ashraf et al [ 25 ] reported that the foliar application of TNAU pulse wonder improved the seed yield in pulses. El-Fouly et al [ 26 ] reported that the foliar application of nutrients to maize resulted in increased grain yield.…”
Section: Introductionmentioning
confidence: 98%